Demokracja a państwo prawa - Grochowski, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The paper aims to demonstrate the meaning of the notions of democracy and a state of law in relation to the Constitution as the fundamental law. All these issues are related to the contemporary social and political situation of Poland and the European Union. It is observed that in the state of law, civic fredoms and rights are helpful in separating the public from the private. Democracy is the rule of the people who need to be headed by a direct ruler. The notions of the ‘state of law’ and ‘democracy’become mutually related to the Constution, referred to as the fundamental law. The paper shows the contemporary status of democracy, compared to the state of law, and it provokes the question whether we should lay our own foundations of democracy which wouldspond to our social and political reality.